2020
DOI: 10.1049/iet-ipr.2019.0800
|View full text |Cite
|
Sign up to set email alerts
|

3D reconstruction of spine image from 2D MRI slices along one axis

Abstract: Magnetic Resonance Imaging (MRI) is a technology for non-invasive imaging of anatomical features in detail. It can help in functional analysis of organs of a specimen but it is very costly. In this work, methods for (i) virtual three-dimensional (3D) reconstruction from a single sequence of twodimensional (2D) slices of MR images of a human spine and brain along a single axis, and (ii) generation of missing inter-slice data are proposed. Our approach helps in preserving the edges, shape, size, as well as the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Nevertheless, missing differences between groups, especially at the pole of a longitudinal brain structure, cannot be excluded. On the other hand, it was shown that interslice distances up to 5 mm do not markedly reduce accuracy or provide an obstacle to reliable comparisons in humans when using bicubic or bilinear interpolation as implemented in SPM (Ghoshal et al, 2020 ). Importantly, imaging protocols were identical for all dogs, which strongly limits potential inaccuracies in any assessment (Schmidt et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, missing differences between groups, especially at the pole of a longitudinal brain structure, cannot be excluded. On the other hand, it was shown that interslice distances up to 5 mm do not markedly reduce accuracy or provide an obstacle to reliable comparisons in humans when using bicubic or bilinear interpolation as implemented in SPM (Ghoshal et al, 2020 ). Importantly, imaging protocols were identical for all dogs, which strongly limits potential inaccuracies in any assessment (Schmidt et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this method does not require manual intervention, it has many steps and is easy to accumulate errors, affecting the final reconstruction model's accuracy. In addition, there are some methods based on MRI images [13], which can provide richer soft tissue information and help in the diagnosis and evaluation of spinal diseases. However, this type of method is easily affected by resolution and noise, the obtained reconstruction accuracy is not high, resulting in poor subsequent evaluation effects, and it is also difficult to handle complex morphology and structure.…”
Section: Related Workmentioning
confidence: 99%
“…The three‐dimensional (3D) reconstruction of tissues is an approach increasingly used to visualize the detailed anatomy of whole‐body regions and specific tissues (Ghoshal et al, 2020; Tongdee et al, 2006). This methodology has been particularly valuable for elucidating the intricate 3D architecture and anatomical relationships of various nerves and plexuses (Karam et al, 2005; Moszkowicz, Alsaid, Bessede, Penna, et al, 2011), which are often microscopic in nature and therefore difficult to fully appreciate using gross dissection approaches alone.…”
Section: Introductionmentioning
confidence: 99%